Demography and the Graeco-Roman world new insights and approaches - Holleran, Claire, 1979-; Pudsey, April (Cambridge University Press, 2011)
"Through a series of case studies this book demonstrates the wide-ranging impact of demographic dynamics on social, economic and political structures in the Graeco-Roman world. The individual case studies focus on fertility, mortality and migration and the roles they played in various aspects of ancient life. These studies - drawn from a range of populations in Athens and Attica, Rome and Italy, and Graeco-Roman Egypt - illustrate how new insights can be gained by applying demographic methods to familiar themes in ancient history. Methodological issues are addressed in a clear, straightforward manner with no assumption of prior technical knowledge, ensuring that the book is accessible to readers with no training in demography. The book marks an important step forward in ancient historical demography, affirming both the centrality of population studies in ancient history and the contribution that antiquity can make to population history in general"--